Recurrent urinary tract infections: a critical review of the currently available treatment options. (13th February 2020) - Negus, Mike; Phillips, Christian; Hindley, Richard
Abstract : Key content: Urinary tract infections (UTIs) are the most common infections in women worldwide. Prevalence increases with age to 20% over the age of 60. Recurrence is common. UTI is a clinical and socio‐economic burden and a cause of significant psychological distress to the patient. Acute UTI needs swift assessment, diagnosis and treatment to prevent ascending or systemic infection. Antibiotics remain the mainstay of treatment in acute UTI; it is thought that up to 50% of antibiotic prescriptions are inappropriate or unnecessary and may increase the risk of bacterial resistance. Management strategies to prevent recurrent UTI are heterogeneous. Learning objectives: To understand the rationale of why preventing recurrent UTI (rUTI) is important. To develop an awareness of the non‐physical effects of rUTI. To understand the critical appraisal of the current and developing treatments for rUTI.